Delayed Clamping of Umbilical Cord and Risk of Intraventricular Hemorrhage in Preterm Babies at Souq Alkamees Hospital, Libya - Khalifa Abu Faris,; Belkasem Abdurahman,; Abdul Aziz Abu Ras, (AlQalam Journal of Medical and Applied Sciences, 2026)
Delayed umbilical cord clamping appears to be beneficial for term and preterm infants. Delayed cord clamping (DCC) improves neurologic outcomes in preterm infants through a reduction in intraventricular hemorrhage (IVH) incidence. In term infants, delayed umbilical cord clamping increases hemoglobin levels at birth and improves iron stores in the first several months of life. In preterm infants, delayed umbilical cord clamping is associated with significant neonatal benefits, including improved transitional circulation, better establishment of red blood cell volume, decreased need for blood transfusion, and lower incidence of necrotizing enterocolitis and intraventricular hemorrhage. This study aimed to determine whether delayed umbilical cord clamping is associated with a reduced risk of Intraventricular hemorrhage in preterm babies. The study was conducted at Alkhoms Teaching Hospital, Libya, with 182 cases during the study period, October 2023 to September 2024. In this study, males account for 50.54% and females for 49.45%. The gestational age is denoted in weeks, from 24 weeks to 27 weeks is 19.78%, and from 28 weeks to 31 weeks is 80.21%. The birth weight of the babies varies from 2500 to 4000 grams. The weights 2500 to 3000 g are 16.48%, 3000 to 3500 g are 52.74%, and 3500 to 4000 g are 30.76%. In this table, the time between delivery and cord clamping is noted. First, less than or equal to 10 seconds is 5.49%, 11 to 30 seconds is 6.04%, 31 to 59 seconds is 42.85%, and greater than 60 seconds is 46.11%. The infant death rate in vaginal deliveries is 1.09% and in cesarean deliveries is 0.54%. The grade of hemorrhage 1 is 3.29%, 2 is 1.09%, 3 is 0.54%, and 4 is 1.64%, respectively.